1997
DOI: 10.1083/jcb.136.4.907
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Neurite Outgrowth through Contactin and Nr-CAM by Extracellular Regions of Glial Receptor Tyrosine Phosphatase β

Abstract: Receptor protein tyrosine phosphatase β (RPTPβ) is expressed as soluble and receptor forms with common extracellular regions consisting of a carbonic anhydrase domain (C), a fibronectin type III repeat (F), and a unique region called S. We showed previously that a recombinant Fc fusion protein with the C domain (βC) binds to contactin and supports neuronal adhesion and neurite growth. As a substrate, βCFS was less effective in supporting cell adhesion, but it was a more effective promoter of neurite outgrowth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
149
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 67 publications
3
149
0
3
Order By: Relevance
“…Since the discovery of the interactions between PTPRZ and CNTN1 (5), the prevailing notion has been that the transmembrane form of PTPRZ expressed on glial cells interacts in trans with CNTN1 at the surface of axons, promoting glial adhesion and neurite outgrowth (20,28). Our results demonstrate that soluble PTPRZ modulates OPC proliferation via CNTN1 expressed at the surface of OPCs.…”
Section: The Ptprz/cntn1 Complex May Help Recruit Additional Cell Surmentioning
confidence: 47%
See 1 more Smart Citation
“…Since the discovery of the interactions between PTPRZ and CNTN1 (5), the prevailing notion has been that the transmembrane form of PTPRZ expressed on glial cells interacts in trans with CNTN1 at the surface of axons, promoting glial adhesion and neurite outgrowth (20,28). Our results demonstrate that soluble PTPRZ modulates OPC proliferation via CNTN1 expressed at the surface of OPCs.…”
Section: The Ptprz/cntn1 Complex May Help Recruit Additional Cell Surmentioning
confidence: 47%
“…However, these regions are not necessary to bind to CNTN1 (Fig. 2) (20), which suggests that they may help recruit additional molecules at the surface of OPCs. Interestingly, proteins such as the growth factor pleiotrophin, the extracellular matrix glycoproteins tenascin-C and tenascin-R (TNR), and the cell adhesion molecules L1, NrCAM, and CNTN2, have been shown to interact with the FNIII and the spacer regions of PTPRZ (6).…”
Section: The Ptprz/cntn1 Complex May Help Recruit Additional Cell Surmentioning
confidence: 99%
“…[52][53][54][55][56] PTPRZ1 gene products are expressed from early developmental to adulthood in glial cells 47,[57][58][59] as well as in certain population of neurons [60][61][62][63] and are implicated in neuron-glial cell interactions that involve on bi-directional signaling, including myelination and node of Ranvier formation, through interactions with neuronal cell adhesion molecules. 55,56 Interestingly, in situ hybridization analysis has shown that PTPRZ1 is expressed in the subventricular zone of the lateral ventricles in early embryos and in adults, in the subgranular zone in the dentate gyrus of the hippocampus of adults, 57,64 and in adult glial progenitor cells, 65 suggesting that PTPRZ1 also has a function in adult stem/progenitor cells. In addition, it has been shown that inhibition of PTPRZ1 expression or inhibition of RPTPb activity in adult glial progenitors leads to their differentiation into mature oligodendrocytes, 65 supporting a role for RPTPb activity in the maintenance of glial progenitors in an undifferentiated state.…”
Section: Discussionmentioning
confidence: 99%
“…Total IgGs were purified from plasma from all SSc patients and from two normal volunteers, by use of recombinant protein G-Sepharose 4B conjugate (Zymed Laboratories, San Fran-cisco, CA) and disposable spin-out columns (G Biosciences, Maryland Heights, MO) as previously described (42). Briefly, rec-protein G-Sepharose 4B conjugate was diluted 1:10 in 20 mM sodium phosphate pH 7.0, loaded on spin-out columns, and allowed to drain.…”
Section: Methodsmentioning
confidence: 99%